2010 Fifth International Conference on Digital Information Management (ICDIM) 2010
DOI: 10.1109/icdim.2010.5664631
|View full text |Cite
|
Sign up to set email alerts
|

Using Chinese part-of-speech patterns for sentiment phrase identification and opinion extraction in user generated reviews

Abstract: Accelerated growth of the Internet has enabled users worldwide to share their feelings and experiences. User-generated content (UGC) websites are the most abundant sources of user reviews. Accurately identifying sentiment phrases is essential to understand the expressed opinions in user reviews. To achieve this, part-of-speech (POS) patterns of phrases are useful. However, previous studies for Chinese opinion extraction only translate English POS patterns directly into Chinese for this task without considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In terms of opinion words, intransitive stative verbs are the most frequent ones appearing in the gathered reviews that are similar part of speech patterns in Peng and Shih's finding (Peng & Shih, 2010). Finally, 454 opinion words are adopted after text preprocessing and the features selection process.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of opinion words, intransitive stative verbs are the most frequent ones appearing in the gathered reviews that are similar part of speech patterns in Peng and Shih's finding (Peng & Shih, 2010). Finally, 454 opinion words are adopted after text preprocessing and the features selection process.…”
Section: Resultsmentioning
confidence: 99%
“…This approach is not limited to any product, so it has wide applicability. In reference [4], the authors observed Chinese structure and finished in a combination of different parts of speech. They proposed a set of part-of-speech (POS) patterns that may locate opinion words with high accuracy.…”
Section: A Backgroundmentioning
confidence: 98%
“…Reference [4] proposed an opinion extraction method using part of speech pattern to find the location of opinion words. Since CKIP POS tag is streamline POS, and their POS is a simplified mark, we converted to streamline POS tags and recombination.…”
Section: Establish Opinion Dictionarymentioning
confidence: 99%
“…However, word segmentation remains a time-consuming and context-dependent task. Besides above issues, preprocessing steps such as stop-words removal, stemming and synonym matching are also frequently required in those word-based methods. Some techniques even need to analyze the POS (Part of Speech) of each word, which increases the cost and the complexity of the sentiment identification (Peng and Shih, 2010). As the advances in social media platforms, people are no longer satisfied with receiving information passively, and they are also willing to express their own opinions and emotions through online.…”
Section: Related Workmentioning
confidence: 99%